Across the Apocalypse on Horseback: Imperfect Legal Responses to Biodiversity Loss - Jim Chen (Washington University Journal of Law & Policy, 2005)
Life on Earth overcomes mass extinction events on a temporal scale spanning millions of years. By this measure, “the loss of genetic and species diversity” is probably the contemporary crisis “our descendants [will] most regret” and “are least likely to forgive.” Biodiversity loss is the “scientific problem of greate[st] immediate importance for humanity.” If indeed biodiversity loss has reached apocalyptic proportions, it is fitting to describe the engines of extinction in equine terms. Jared Diamond characterizes the deadly horsemen of the ecological apocalypse as an “Evil Quartet” consisting of habitat destruction, overkill, introduced species, and secondary extinctions. Edward O. Wilson prefers an acronym derived from the Greek word for horse. HIPPO represents Habitat destruction, Invasive species, Pollution, Population, and Overharvesting. Although conservation biologists have identified the leading causes of biodiversity loss, legal responses to the crisis do not address distinct sources of human influence on evolutionary change. Not surprisingly, legal scholarship tends to ignore the distinctions among causes of biodiversity loss. This Essay takes a modest step toward remedying at least the latter shortcoming.
Keywords: Biodiversity; Endangered species